Behavior feedback and Need for Cognition: factors affecting coffee beverage consumption - Gallivan, Nicholas P. (Kansas State University, 2020)
The purpose of this study was to investigate whether one’s tendency to engage in and enjoy cognitive activity (i.e., Need for Cognition) affects both individuals’ intention to consume high-cost, high calorie “specialty” coffee drinks and their likelihood to reduce consumption of these drinks after reading a persuasive behavior feedback message. Through an online survey, participants viewed one of four messages: a personalized behavior feedback message, a generic feedback message that contained a memory prompt, a generic feedback message that did not contain a memory prompt, and no message. Pre- and post-intervention measures of specialty coffee drink consumption and participants’ likelihood to reduce their consumption were recorded, and participants’ levels of Need for Cognition were also assessed. Although each of the three behavior feedback messages were successful at encouraging reduced specialty coffee drink consumption compared to the no message control, an interaction effect between Need for Cognition Scale scores and behavior feedback message condition was not established, suggesting that no differences in post-intervention consumption intention were established between individuals of varying levels of Need for Cognition when presented with differing forms of behavior feedback persuasive messages. Furthermore, Need for Cognition predicted both post-intervention specialty coffee consumption intention and likelihood of reducing consumption "in the next few days," but in a surprising manner. Clarification of these results, limitations of the study's methodology, and future research possibilities are also discussed.
Keywords: Need for Cognition; Behavior feedback; Health interventions; Tailored messages; Behavior intention; Coffee consumption